Assessment of Transfusion Transmitted Infections Among Blood Donors from Peshawar: A Cross-Sectional Study - Ullah, Mati; Mahmood, Azhar; Ahmad, Waqar; Matiullah, .; Ullah, Irfan; Ullah, Majeed; Islam, Haris; Ali Shah, Syed Amir; Iqbal, Muhammad; Ali, Ihsan (Biological and Clinical Sciences Research Journal, 2025)
Blood transfusion is life-saving yet carries the risk of transfusion-transmitted infections (TTIs)—notably hepatitis B (HBV), hepatitis C (HCV), HIV infection, syphilis, and malaria—risks that are disproportionately higher in many low- and middle-income settings. Robust local surveillance among blood donors is crucial for informing screening policies and donor recruitment strategies. Objective: To estimate the prevalence and pattern of TTIs among blood donors at the Regional Blood Centre (RBC), Peshawar, and to describe donor characteristics, ABO distribution, and co-infections. Methods: This cross-sectional study was conducted at the RBC in Peshawar, Pakistan, from January 1 to June 30, 2023. A total of 1,700 consecutive, apparently healthy blood donors were included in the study. Donor demographics (age, sex), donor type (regular vs replacement), haemoglobin (Hb), ABO blood group, and TTI screening results were extracted from routine records. All donations were screened for HBV, HCV, HIV, syphilis, and malaria according to the RBC's standard serologic screening algorithm; reactivity was defined according to the manufacturer's instructions. We summarised data using proportions with 95% confidence intervals (CIs). Group differences were explored with χ²/Fisher's exact tests; two-sided p<0.05 was considered statistically significant. Results: Among 1,700 donors, 99.8% (1,697/1,700) were male and 0.2% (3/1,700) were female. Most donors were aged 18–26 years (46.5%, 790/1,700) or 27–35 years (40.7%, 691/1,700); the remainder were 36 years or older (12.9%, 219/1,700). Replacement donors predominated (99.6%, 1,693/1,700) with only 0.4% (7/1,700) regular donors. The overall prevalence of any TTI was 4.9% (84/1,700; 95% CI, 3.9–6.0). By pathogen, prevalence was: HBV 2.6% (45/1,700; 95% CI, 1.9–3.4), HCV 1.0% (17/1,700; 95% CI, 0.5–1.5), syphilis 0.9% (15/1,700; 95% CI, 0.4–1.3), and HIV 0.4% (7/1,700; 95% CI, 0.1–0.7). No donor screened positive for malaria (0/1,700; upper 95% CI ≈0.18%). One donor (0.06%) had dual reactivity for HBV and HCV. ABO distribution was A 28.9% (491/1,700), B 32.8% (559/1,700), AB 10.5% (179/1,700), and O 27.7% (471/1,700); the distribution was significantly non-uniform (χ², p<0.0001). Hb concentrations were <13 g/dL in 0.06% (1/1,700), 13–14 g/dL in 1.7% (29/1,700), 15 g/dL in 60.5% (1,028/1,700), 16 g/dL in 30.9% (525/1,700), and 17 g/dL in 6.9% (117/1,700). Conclusion: TTIs were detected in approximately one in twenty donations, with HBV contributing the largest share. The near-exclusive reliance on replacement donors highlights a critical need to strengthen voluntary, non-remunerated donor recruitment, maintain rigorous and standardised screening with quality assurance, and provide post-donation counselling and linkage to care to reduce TTI risk further and enhance blood safety in this setting.